2017
DOI: 10.3390/molecules22030409
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activities of Ethyl 2-(2-pyridylacetate) Derivatives Containing Thiourea, 1,2,4-triazole, Thiadiazole and Oxadiazole Moieties

Abstract: Thirty six novel heterocyclic derivatives of ethyl 2-(2-pyridylacetate) were efficiently synthesized. The new compounds involve the linkage of a 2-pyridyl ring with thiosemicarbazide (compounds 1–7), 1,2,4-triazole (compounds 1a–7a), 1,3,4-thiadiazole (compounds 1b–7b), and 1,3,4-oxadiazole (compounds 1f–7f) moieties. The last group of compounds 1e–7e involves the connection of a 2-pyridyl ring with 1,2,4-triazole and thiourea. 1H-NMR, 13C-NMR and MS methods were used to confirm the structures of the obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The series of 5-(pyridin-2-ylmethyl)-1,3,4-thiadiazol-2-amine derivatives 11-16 were synthesized by intramolecular cyclization of the corresponding hydrazinecarbothioamides under acidic conditions and the activity against HIV-1 was tested on MT-4 cells by MTT assay using efavirenz as a standard drug [64]. Molecular modeling studies for the pyrimidyl derivative 10 showed the formation of two potential intermolecular hydrogen bonds involving a nitrogen atom and the amino group of the thiadiazole ring and aminoacids from NNBS of RT.…”
Section: -10mentioning
confidence: 99%
See 2 more Smart Citations
“…The series of 5-(pyridin-2-ylmethyl)-1,3,4-thiadiazol-2-amine derivatives 11-16 were synthesized by intramolecular cyclization of the corresponding hydrazinecarbothioamides under acidic conditions and the activity against HIV-1 was tested on MT-4 cells by MTT assay using efavirenz as a standard drug [64]. Molecular modeling studies for the pyrimidyl derivative 10 showed the formation of two potential intermolecular hydrogen bonds involving a nitrogen atom and the amino group of the thiadiazole ring and aminoacids from NNBS of RT.…”
Section: -10mentioning
confidence: 99%
“…The series of 5-(pyridin-2-ylmethyl)-1,3,4-thiadiazol-2-amine derivatives 11-16 were synthesized by intramolecular cyclization of the corresponding hydrazinecarbothioamides under acidic conditions and the activity against HIV-1 was tested on MT-4 cells by MTT assay using efavirenz as a standard drug [64]. …”
Section: -10mentioning
confidence: 99%
See 1 more Smart Citation
“…Heterocyclic rings are important chemical scaffolds in the search for novel pesticides. Approximately 70% of pharmaceuticals and agrochemicals contain at least one heterocyclic moiety, and as one of the most important, the 1,3,4‐oxadiazole ring is reported to possess a wide variety of biological activities, including antibacterial, antifungal, antiviral, insecticidal and herbicidal . For instance, Guimarães et al .…”
Section: Introductionmentioning
confidence: 99%
“…The prospect of pharmaceutical research remains the search for biologically active substances among molecules that combine heterocyclic moieties of different nature [1][2][3][4][5][7][8][9]. Examples of such fragments are 1,2,4-triazole and thiadiazole, which have significant synthetic and pharmacological potential [6].…”
mentioning
confidence: 99%